Wartości funkcjonariuszy Służby Więziennej - Lenart-Kłoś, Katarzyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of this paper is to present values of Prison Service officers, who work in the total institution and thereby constitute one of the dispositional groups. The so called “common” and “higher” values will be discussed in the light of sociological research carried out among warders working directly with the inmates, as well as compared with selected research on values, available in sociological literature. Since the 1990s. in Polish penitentiary system far-reaching transformations have been made. The most significant alterations are to be found in the way prison role as an institution is being perceived. The main purpose of an imprisonment sentence is no longer viewed as retaliation taken on the offender. Nowadays prison is perceived as a place of improvement. At the same time, expectations for prison staff have changed as well. Warders became mediator of those imprisoned with the rest of society. Currently, prison officers are being faced with high expectations, also in the field of professional ethics. It is therefore significant to identify anew values that make up the axiological foundations of prison service, as values determine the criteria of decision making in both private and professional life, particularly under the demanding circumstances of work in total institution.